Computer Vision and Graphics International Conference, ICCVG 2016, Warsaw, Poland, September 19-21, 2016, Proceedings - Chmielewski, Leszek J.; Datta, Amitava; Kozera, Ryszard; Wojciechowski, Konrad (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2016)
This book constitutes the refereed proceedings of the International Conference on Computer Vision and Graphic, ICCVG 2016, held in Warsaw, Poland, in September 2016. The 68 full papers presented were carefully reviewed and selected from various submissions. They show various opportunities for valuable research at the border of applied information sciences, agribusiness, veterinary medicine and the broadly understood domains of biology and economy. .